Factors Affecting Ownership Strategies in International Joint Ventures - Iso-Pietilä, Mika (My University, 2001)
The main objective of the study is to determine how firm-, host- country and investment related factors affect firms' different ownership alternatives at entry and ownership instability in international joint ventures. The point of view that has been taken is that of a foreign investor. First the basic characteristics of joint ventures are presented. These include definition, classification, advantages, motives and disadvantages of joint ventures. Second, firm-, host country- and investment related factors affecting ownership arrangement at entry are analysed. Next, factors affecting ownership instability are analysed. Hypotheses are then developed and to be tested in the empirical part of the study. Empirical part of the study is based on database gathered at the department of marketing at the University of Vaasa. The total number of international joint ventures in the sample was 758 formed by 161 Finnish firms. The joint ventures were located both in developed and less developed countries. Crosstabulations, chi-square test and frequencies were used for statistical analysis of the results. The empirical results supported 8 of the original 25 hypotheses. In some cases the results obtained were not the ones expected. The results indicated that culture distance, physical distance, government policies, stage of development, form of investment and number of partners were the most significant determinants of ownership arrangement at entry. The most significant determinants of joint venture instability were size of investing firm, international experience, stage of development, form of investment and age of the joint venture.
Keywords: International joint ventures; ownership arrangement; instability.; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|